Implementasi Pendampingan Pembukuan Kas Sederhana untuk Meningkatkan Administrasi Keuangan Pelaku Usaha Sarolangun - Tri Wera Agrita; Titis Wulandari; Aura Parastikha (Jurnal Pengabdian Pendidikan Masyarakat (JPPM), 2026)
Micro, Small, and Medium Enterprises have a strategic role in regional growth, one of which is in Bathin VIII District, Sarolangun. However, the results of the situasion analysis show that the majority of business actors have not implemented cash bookkeeping neatly and regularly. The problems faced by business actors are low financial literacy, not only the routine recording of incoming and outgoing cash, but also the mixing of business finances with personal finances. This condition causes business actors to experience difficulties in knowing profit and loss, determining selling prices, and making data-based business decisions. The aim of this service is to improve the orderly financial administration of business actors through the implementation of simple cash bookkeeping assistance. The implementation method uses an approach that involves participation which consists of several stages, namely preparation, socialization, training and mentoring. Mentoring is carried out through direct practce of manual cash bookkeeping and the use of smartphone-based financial recording applications that are easily accessible to business actors. The results of the activity show an increase in understanding and skills of business actors in recording financial transantions in an orderly, systematic and sustainable manner. Business owners are starting to be able to separate personal and business finance and understand cash flow and profit and loss conditions more accurately. Therefore, this activity helps strengthen the financial management of MSMEs and supports the improvement and competitiveness of micro-businesses in Sarolangun Regency.